POTENSI LESTARI IKAN LAYANG (Decapterus spp) BERDASARKAN HASIL TANGKAPAN PUKAT CINCIN DI PERAIRAN TIMUR SULAWESI TENGGARA - Amir Mahmud; Rita L. Bubun (Fakultas Perikanan dan Ilmu Kelautan, 2015)
Decapterus spp is one of small pelagic fish species having potential and high economic value in Southeast Sulawesi. The utilization of resources activities in East Southeast Sulawesi is using the purse seine units. Study aim was to determine of the maximum sustainable yield (MSY) and catches of the Decapterus spp allowed (JTB) in the East Southeast Sulawesi waters. This research was using survey method to get a represented potential of Decapterus spp in the East Southeast Sulawesi waters. The approach done by means of analyzed data efforts and the catch data of Decapterus spp by using the purse seine unit in Pelabuhan Perikanan Samudera Kendari. The results about the potential fish a sustainable (Decapterus spp) were : the maximum sustainable yield (MSY) of Decapterus spp : 5.747.61 tonnes/years and catches of Decapterus spp allowed (JTB) 4.598 tonnes/ year.